PENGARUH LIABILITAS DAN EKUITAS TERHADAP LABA BERSIH PT BANK RAKYAT INDONESIA (PERSERO) TBK PERIODE 2015-2022 - Inggrit Frilly Sahetapy (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2023)
Banks are financial institutions that continue to generate profits for their sustainability. The objectives of this study are: To determine the effect of liabilities and equity on net income at PT Bank Rakyat Indonesia Tbk for the 2015-2022. The subject of this research is the quarterly financial statements of PT Bank Rakyat Indonesia Tbk for the 2015-2021 Period. The research method used in this thesis is quantitative, multiple regression statistical analysis method to see the effect of liabilities and equity on net income at PT Bank Rakyat Indonesia Tbk 2015-2022. The results of this study indicate that the results of the multiple linear regression analysis equation are Y = 9.822 + (-0.026) X1 + (0.198) X2. The results of the T test liabilities have no significant effect while equity has a significant effect on net income. Simultaneously through the F test is that liabilities and equity have a significant effect on net income. The coefficient of determination test results show an R square value of 32.2%, meaning that liabilities and equity have a 32.2% contribution to net income. This shows that the increase in liabilities and equity will increase net profit at PT Bank Rakyat Indonesia.